Assessing Residences’ Climatic Compatible Comfort Approach to Low-Cost Low Energy Consume Strategies, Case Study: Qazvin City, Iran - Farnood Freidooni; Amir Gandomkar; Saghar Freidooni (Sustainable Earth Trends)
Climatic conditions inside and outside buildings are one of the most influential factors affecting human comfort. Considering the increase in population, pollution, and energy crises, providing climatic comfort conditions inside the building is a significant issue. compatibility with the climate and consuming less energy is the right approach to overcome this crisis. The purpose of the present study is to investigate the climatic comfort conditions and optimize energy consumption (approached to zero-energy strategies) in buildings of Qazvin City, Iran. The data of 29 climatic parameters of the Qazvin synoptic station were used during the statistical period of 2000-2020. The climatic comfort range of Qazvin city was checked. Then, climatic-compatible comfort conditions and optimization of energy consumption in the buildings were analyzed with four different comfort models. The results showed which months have comfortable or uncomfortable conditions in each of the studied parameters. The examination indicates that the approach to ASHRAE 55 comfort, Comfort 2013, Adaptive comfort, and ASHRAE 2005 model, respectively, 12.4%, 9%, 9.2%, and 7.2% of the year (1085, 785, 810, and 632 hours), the buildings of are within the natural comfort range. The zero-energy design strategies i. e. Small well-insulated skylight windows, minimize or eliminate west-facing glazing, efficient natural ventilation, low-pitched roofs with wide overhangs, etc. enhance residences’ climatic compatible comfort. The results of the comparison of climate-compatible comfort strategies with existing situations suggested that the high energy consumer, costly ineffectiveness utilities, and building design are used to supply the residents’ comfort.